Examining the Influence of Organisational Culture and Situational Variables on Deviant Work Practices Among Government Employees - Vahid Rooholelm; Mohammad Taleghani; Eva Desembrianita (PT. Mawadaku Sukses Solusindo, 2025)
Purpose – This research investigates the extent to which situational factors drive organisational deviance and explores the mediating influence of organisational culture among employees in the public sector. Aim(s) – The objective was to identify key predictors of deviant workplace behaviour within public service organisations and to examine how organisational culture moderates the impact of these predictors. Design/methodology/approach – Adopting a quantitative research strategy, the study applied a cross-sectional survey design with 250 respondents. Data analysis utilized regression techniques alongside structural equation modeling to test the mediating role of organizational culture. Findings – Results from the structural equation modeling demonstrate that perceived injustice, heightened stress, and inadequate support contribute significantly to workplace deviance. Specifically, organizational injustice and work-related stress emerged as strong predictors of deviant behavior, while organizational culture mediated the effects of these variables. Limitations of the study – The findings may be affected by sampling error and potential response bias due to reliance on self-reported data. Furthermore, the exclusive focus on public service limits the generalizability of the conclusions to other sectors. Practical implications and Originality/value – The study enhances existing scholarship on the mediating function of organizational culture in deviant workplace behavior. It further illustrates how fostering a strong organizational culture can serve as a mechanism to mitigate or prevent workplace deviance among employees tasked with implementing organizational policies